SITUS PALAS PASEMAH SEBAGAI SUMBER PEMBELAJARAN SEJARAH LOKAL DI PROGRAM STUDI PENDIDIKAN SEJARAH STKIP PGRI BANDAR LAMPUNG - Siska, Yulia (Lentera: Jurnal Ilmiah Kependidikan, 2014)
This study aimed to determine 1) heritage (Palas Inscription Pasemah ) that can be used as a source of learning local history, 2) the value obtained pedagogic students and professors in Palas Pasemah site as a learning resource, and 3) Appreciation of students when using relics in the world as a source of learning Palas Pasemah local history.This study used qualitative methods with case studies of single spikes (embedded research). Data collection techniques using literature techniques, library research, observation, and content analysis. The validity of the data using triangulation of data and triangulation methods. Analysis of data using interactive analysis with the three stages of analysis.The results showed that: 1) a collection of archaeological sites were used to study the local history is a King Sriwijaya Promised Sriwijaya inscription containing a curse and a threat to those who oppose or do not want to devote to the King of Srivijaya; 2) The value obtained pedagogic students and faculty is either: a ) the value of the field of religion and belief; b ) the value of culture; and c) the value of the field of law and government; and 3) Palas Pasemah site as a learning resource has been run up to the local history by utilizing the teaching of historical living history based on the student to deliver the understanding and awareness of its own history.